Indexes for the assessment of bacterial pollution in bathing waters from point sources: The northern Adriatic Sea CADEAU service. (1st September 2021) - Bruschi, Antonello; Lisi, Iolanda; De Angelis, Roberta; Querin, Stefano; Cossarini, Gianpiero; Di Biagio, Valeria; Salon, Stefano; Solidoro, Cosimo; Fassina, Daniel; Ancona, Sara; Silvestri, Cecilia
Abstract: This paper presents a novel set of water quality indexes to identify the area potentially affected by point sources of bacterial pollution in coastal bathing waters. The indexes, developed in the framework of the CADEAU service, are evaluated on the results of a modelling system based on the integration of a high-resolution ocean model, remote sensing observations and in situ monitoring data for the northern Adriatic Sea. In particular, the system is a downscaling of the Mediterranean Copernicus Marine Environment Monitoring Service and exploits data produced within the Bathing Waters Directive, the Water Framework Directive and the Urban Waste Water Treatment Directive to create added value products. The aim of the proposed indexes is to support the identification of areas of influence for bathing waters by identifying the potential threat from point sources of bacterial pollution, both in standard conditions and peculiar events such as a total bypass of wastewater treatment plants. The results for the Chioggia Municipality case study show the potential of the indexes to significantly improve the geographical identification and quantitative evaluation of the impacts of bacterial pollution sources on bathing waters, facilitating the design of mitigation measures. The proposed methodology represents a new management approach to support local authorities in defining the area of influence within the water bathing profile through the proper characterization of the point sources of bacterial pollution. Highlights: Spatio-temporal variability of bacterial pollution from point sources is modelled. The system takes advantage of in situ data from official monitoring protocols. Indexes are presented for characterizing the area of influence of bathing water. Impact from mean discharge and total bypasses from point sources is estimated. The indexes may identify potential sources of short-term pollution events.